'If I die, I die, I don't care about my health': Perspectives on self‐care of people experiencing homelessness. (6th September 2019) - Paudyal, Vibhu; MacLure, Katie; Forbes‐McKay, Katrina; McKenzie, Myra; MacLeod, Joan; Smith, Ann; Stewart, Derek
Abstract: Self‐care, which refers to what people do to prevent disease and maintain good health, can alleviate negative health consequences of people experiencing homelessness. The aim of the study was to apply a theoretically informed approach in exploring engagement of people experiencing homelessness in self‐care and to identify factors that can be targeted in future health and social care interventions. Qualitative semi‐structured interviews were conducted with 28 participants opportunistically recruited from a specialist homelessness healthcare centre of North East Scotland, the United Kingdom (UK). An interview schedule was developed based on the theoretical domains framework (TDF). Interviews were audio‐recorded and transcribed verbatim. Six aspects of self‐care were explored, including (a) self‐awareness of physical and mental health, (b) health literacy, including health seeking behaviour, (c) healthy eating, (d) risk avoidance or mitigation, (v) physical activity and sleep and (e) maintaining personal hygiene. Thematic analysis was conducted by two independent researchers following the Framework Approach. Participants described low engagement in self‐care. Most of the barriers to engagement in self‐care by participants were related to 'environmental context and resources' domain of TDF. Participants often resorted to stealing or begging for food. Many perceived having low health literacy to interpret health‐related information. Visits to churches and charities to get a shower or to obtain free meals were commonplace. Participants expressed pessimism that there was 'nothing' they could do to improve their health and described perceived barriers often too big for them to overcome. Alienation, lack of social support and the perception that they had done irreversible damage to their health prevented their involvement in self‐care. The theme of 'social circle' held examples of both enabler and barriers in participants' uptake of risky behaviours. Health and social services should work with persons experiencing homelessness in designing and delivering targeted interventions that address contextual barriers, multi‐morbidity, health literacy and self‐efficacy.